2007
DOI: 10.1111/j.1600-0633.2007.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reproductive timing and hatch date on fathead minnow recruitment

Abstract: Divino JN, Tonn WM. Effects of reproductive timing and hatch date on fathead minnow recruitment.Abstract -Timing of reproduction can be an important determinant of recruitment success for fish in strongly seasonal environments, both for individuals hatching at different times over extended spawning seasons and for entire cohorts, if the spawning period is accelerated or delayed among years. To examine potential demographic consequences of delayed spawning, we staggered dates that fathead minnow (Pimephales pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…We developed a stochastic, density-dependent, stage-structured population model that tracks eggs and larvae daily, juveniles weekly, and adults annually for 120 years. The model was parametrized using life-history values extracted from well-studied, wild populations in Alberta, Canada [49][50][51][52], and modified to include our exposure-associated empirical estimates of larval mortality. Each model year spans 365 days and begins with size-independent spawning on July 25 (the median spawn date reported in [51]).…”
Section: Population Projection Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…We developed a stochastic, density-dependent, stage-structured population model that tracks eggs and larvae daily, juveniles weekly, and adults annually for 120 years. The model was parametrized using life-history values extracted from well-studied, wild populations in Alberta, Canada [49][50][51][52], and modified to include our exposure-associated empirical estimates of larval mortality. Each model year spans 365 days and begins with size-independent spawning on July 25 (the median spawn date reported in [51]).…”
Section: Population Projection Modellingmentioning
confidence: 99%
“…The model was parametrized using life-history values extracted from well-studied, wild populations in Alberta, Canada [49][50][51][52], and modified to include our exposure-associated empirical estimates of larval mortality. Each model year spans 365 days and begins with size-independent spawning on July 25 (the median spawn date reported in [51]). Each female in the model produces eggs that take approximately 7 days to hatch at a mean incubation temperature of 20.98C [51,52] (table 1).…”
Section: Population Projection Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the over-winter survival results are not definitive because of the lack of replication, they are consistent with several previous studies of centrarchids, which have showed that YOY hatched earlier in the spawning season make a disproportionately high contribution to the entire year-class [ 14 , 50 , 51 , 52 ]. An over-winter survival advantage for larger-bodied (early born) progeny has also been reported in a European cyprinid, the roach Rutilus rutilus [ 53 ], as well as several North American species [ 16 ], including fathead minnow Pimephales promelas [ 54 ], pumpkinseed [ 55 ], and bluegill Lepomis macrochirus [ 14 ].…”
Section: Discussionmentioning
confidence: 95%
“…To partition the effects of potential growth and sizeselective mortality across the winter, we employed empirical quantile-quantile (QQ) and increment plots [15,40], a combined approach that has been applied to a variety of species [41][42][43][44][45]. For the QQ plots, total length at quantiles 1, 5, 10, 25, 50, 75, 90, 95, and 99 of the size distribution was determined from the length-frequency histograms (i.e., when n > 50; [46]) for the fall and subsequent spring samples, and were plotted against each other.…”
Section: Size-selective Overwinter Mortality and Growthmentioning
confidence: 99%